(3ebOeI aj GdJMdjd Gdcej (B- (3CSGSjGJ JMdjd GdbQGQ hGdJNGPg (B- (3TLQI GdbQGQGJ hfXQjI GdefaYI (B- (3SdGSd eGQcha (B-(3fXQjI GdeHGQjGJ (B-(3GdHQeLI GdNWjI (B-(3GdHQeLI HGdCYOGO GdUMjMI (B-(3GdHQeLI GdOjfGejcjI (B-(3JMdjd THcGJ GdCYeGds - (3YdGA(B, (3GdZQHGhjs ((3GdEScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s)
(3JfGhd gPG GdcJGH GdCSGdjH GdcejI aj GdEOGQI , MjK bOe ef NdGd aUhd OQGSJg ebOeI aj GdJMdjd Gdcej h CSGSjGJ JMdjd GdbQGQ hGJNGPg, h TLQI GdbQGQGJ hfXQjI GdefaYI, ceG JMOK Yf SdGSd eGQcha h fXQjI GdeHGQjGJ HGdGVGaI Gdi GdHQeLI GdNWjI hGdHQeLI HGdCYOGO GdUMjMI hGdHQeLI GdOjfGejcjI hCNjQG JMdjd THcGJ GdCYeGd(B.s
(3HHdjhZQGajG U(B.351s
Keywords: (3GdEOGQI (B- (3GdJMdjd Gdcej s; (3GdJMdjd Gdcejs